Genealogy and Fiction in Hardy - O´Toole, T. author. aut Link
IX, 195 p.
Keywords: Tess O'Toole uncovers Hardy's career-long fascination with the points of intersection between genealogy and fiction and argues that this relationship fuels much of his writing. Hereditary patterns are the product of narrative compulsion; the circulation of the family story is necessary to reproduce the history it records. As well as analyzing Hardy's characteristic treatment of family history, this volume revises existing accounts of genealogical narrative, and in its conclusion considers the presence in other nineteenth- and twentieth-century novels of motifs foregrounded in Hardy's work.